Strategi pemerintah Indonesia dalam Diplomasi Kemanusiaan ke Konflik Rohingya-Mynamar Tahun 2017 - Abdul Halim; Aninda Nuraygy H; Zulfikri Suleman; Annada Nasyaya (Andalas Institute of International Studies, 2022)
The Rohingya Muslim ethnicity has long experienced structural violence and direct violence. Structural violence in the form of restrictions on access to needs is felt by the Rohingya Muslims in the economic, political, social, and cultural sectors. Meanwhile, direct violence took the form of ethnic cleansing, which claimed thousands of lives, and hundreds of thousands of people evacuated themselves to other countries. However, the Myanmar government has closed all access to humanitarian aid by closing itself off from the international community. The Indonesian people took several actions that condemned what had happened to the Rohingya Muslim ethnic. Indonesia uses the path of Humanitarian Diplomacy in this conflict. Indonesia is the first and only country that Myanmar has accepted to have a dialogue with its official officials. The researcher discusses the Indonesian government's strategy in humanitarian diplomacy with Myanmar. The researcher found that the foreign policy of Humanitarian Diplomacy carried out by Indonesia was influenced by 4 Bureaucratic Influencers, namely the President of the Republic of Indonesia, the House of Representatives, the Minister of Foreign Affairs of Indonesia, and the Ministry of Foreign Affairs of the Republic of Indonesia. In this study, the author uses descriptive qualitative research methods based on literature research using secondary data related to the issues raised in this paper.